2019
DOI: 10.1002/jsfa.9869
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐véraison treatment of salicylic acid to enhance anthocyanin content of grape (Vitis vinifera L.) berries

Abstract: BACKGROUND Grape berries produce significant amounts of phenolic compounds. These are an essential qualitative factor due to their nutritional value and effect on berry color and texture. Salicylic acid (SA) and its derivatives usually lead to enhancement of phenolic content in plant tissues. The present study was conducted to evaluate the effect of different levels of SA (0.0, 50.0, 100.0, and 200.0 mM) on the production of phenolic compounds and the derivatives (anthocyanin and flavonoid) in the grape berrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 44 publications
4
31
0
1
Order By: Relevance
“…In the white seeded 'El-Bayadi' cultivar, preharvest SA treatment led to grapes with higher total antioxidants (TA) and total phenolic and flavonoids content at harvest, which was attributed to a delay of the on-plant ripening process [23]. Moreover, SA treatment at pre-veraison stage of 'Sahebi' grapes led to increases not only in total phenolics and flavonoids at harvest but also in anthocyanin concentration, especially in malvidin-3-glucoside, the major anthocyanin in this cultivar [24]. According to these previous reports, we hypothesized that anthocyanin content would be increased by salicylate preharvest treatments in 'Magenta' and 'Crimson' table grapes cultivars, improving their color development and in turn, their market value as well as their antioxidant properties.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…In the white seeded 'El-Bayadi' cultivar, preharvest SA treatment led to grapes with higher total antioxidants (TA) and total phenolic and flavonoids content at harvest, which was attributed to a delay of the on-plant ripening process [23]. Moreover, SA treatment at pre-veraison stage of 'Sahebi' grapes led to increases not only in total phenolics and flavonoids at harvest but also in anthocyanin concentration, especially in malvidin-3-glucoside, the major anthocyanin in this cultivar [24]. According to these previous reports, we hypothesized that anthocyanin content would be increased by salicylate preharvest treatments in 'Magenta' and 'Crimson' table grapes cultivars, improving their color development and in turn, their market value as well as their antioxidant properties.…”
Section: Introductionmentioning
confidence: 83%
“…In grape no previous reports about ASA or MeSa treatments are available in the literature, although a few ones regarding SA treatments were reported. Oraei et al [24] reported that SA spraying treatment, at concentrations from 50 to 200 mM on "Sahebi" cultivar, at pre-veraison stage, led to an increase in phenolic and anthocyanin content. The authors explained these results as the effect of an activation of phenylalanine ammonia lyase (PAL) activity in the vine.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the application of these salicylates during fruit development on trees has been reported to improve fruit quality parameters at harvest. Thus, SA treatment at 0.1 and 0.2 mM of vine (at veraison stage) increased anthocyanin content in berries ( Oraei et al, 2019 ) and SA, ASA, or MeSa treatments (0.5, 1, and 2 mM) applied at three key points of fruit development enhanced sugars, organic acids, and antioxidant compounds in plums at harvest and after storage ( Martínez-Esplá et al, 2017 , 2018 ) as well as in sweet cherries ( Giménez et al, 2014 , 2015 , 2017 ; Valverde et al, 2015 ). In these previous papers, a delay on the postharvest ripening process was also observed, which was attributed to the increased concentration of antioxidant compounds and the activity of antioxidant enzymes.…”
Section: Introductionmentioning
confidence: 94%
“…10 A number of factors and signals influence the accumulation of anthocyanins, including light, temperature, mineral nutrition, and plant growth regulators. [11][12][13] The application of plant growth regulators such as methyl jasmonate (MeJA) is a new approach to effectively improve the color of fruits. 14 Jasmonates (JAs) have been identified as hormones that participate in many physiological processes, including fruit ripening and pigment accumulation.…”
Section: Introductionmentioning
confidence: 99%